Paraplatyptilia terminalis - Ustjuzhanin, P. Ya.; Kovtunovich, V. N. (Zenodo, 2018)
Paraplatyptilia terminalis (Erschoff, 1877) MATERIAL EXAMINED. Khakhassia: Kop'evo, 1.VII 2000, 1♂ (O. Kosterin). DISTRIBUTION. Siberia, NE China, Russian Far East (Kamchatka). Published as part of Ustjuzhanin, P. Ya. & Kovtunovich, V. N., 2018, The fauna of plume moths (Lepidoptera: Pterophoridae) of the Republic of Khakassia, pp. 21-24 in Far Eastern Entomologist 362 on page 22, DOI:10.25221/fee.362.4, http://zenodo.org/record/7168479